Liberty and Suspension in Locke’s Essay - Leisinger, Matthew A (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2021)
I argue for two controversial claims about Locke’s account of liberty in Essay 2.21. The first claim is that Locke does not identify liberty with freedom of action. Instead, Locke places further conditions on liberty beyond to the power to perform or forbear an action at will. The second (and closely related) claim is that Locke takes the power to suspend and examine desire to be necessary for liberty—in other words, that possession of the power to suspend and examine desire is one such further condition upon liberty.